2017
DOI: 10.1080/17530350.2017.1315541
|View full text |Cite
|
Sign up to set email alerts
|

Cryptocurrencies as market singularities: the strange case of Bitcoin

Abstract: Since its creation in 2009 the electronic currency Bitcoin has generated volumes of online debate in the business press. While there have been plenty of economic arguments situating it as a financial bubble about to collapse including from Nobel Prize winning economists; its price value has proven to be more durable than many have predicted. To explain this durability, Karpik's conception of market singularities is used to understand the Bitcoin phenomenon by outlining the beliefs that maintain Bitcoin's statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…We were initially intrigued by how heterogeneity in the Bitcoin community affected entrepreneurship in times of crisis. Extant literature (and our initial exploratory data collection) showed that the initial developers of the Bitcoin infrastructure were known to have had Libertarian tendencies (Dallyn, ). As the infrastructure began to be used by more diverse groups and individuals, however, more ideologies were introduced into the mix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were initially intrigued by how heterogeneity in the Bitcoin community affected entrepreneurship in times of crisis. Extant literature (and our initial exploratory data collection) showed that the initial developers of the Bitcoin infrastructure were known to have had Libertarian tendencies (Dallyn, ). As the infrastructure began to be used by more diverse groups and individuals, however, more ideologies were introduced into the mix.…”
Section: Introductionmentioning
confidence: 99%
“…As the infrastructure began to be used by more diverse groups and individuals, however, more ideologies were introduced into the mix. Recent research into the dynamics of the Bitcoin community have pointed to the friction between those with different ideologies (Dallyn, ), including entrepreneurs (Ingram & Morisse, ).…”
Section: Introductionmentioning
confidence: 99%
“…Our focus on trust underlying mechanisms facilitating the transfer of economic value in payment systems is narrower and more specific than the broader issues of trust involved with mechanisms to maintain the value of currencies. For the latter, see the work of André Orléan (1991Orléan ( , 2000Orléan ( , 2007 and, more specifically in relation to what are more widely referred to as 'crypto-currencies' like Bitcoin, see Dallyn (2017). 02.…”
Section: Resultsmentioning
confidence: 99%
“…However, as Swartz (2018, p. 18) has it, every payment for someone is an act of arbitrage for someone else: liquidity is connected to value in terms of exchangeability of assets with cash. Hence, in order to work as a bridge asset, XRP requires a market and liquidity of its own, (Dallyn 2017). Adoption and market-making constitutes a chicken-and-egg problem for cryptoassets: people will not use an asset until a market has developed around it, and such market will not develop if people do not use the asset (Presthus and O'Malley 2017).…”
Section: ) Define Lets and Time Banks Thuslymentioning
confidence: 99%